Using Learning Platforms to Support Online Learning in Junior High School - Berutu, Nurmala; Hanana, Alna (JURNAL GEOGRAFI, 2023)
The online learning process can be done through various e-learning platforms. The determination of the platform should consider the dimensions of the teacher and those of the students. This study aims to analyze the use of the e-learning platform from the perspective of teachers and students in junior high school. This quantitative research design uses a descriptive method. Participants consisted of 91 teachers and 165 students in Medan City. Data were collected by questionnaire via Google Forms. Quantitative data analysis used descriptive statistics to obtain the percentages for each indicator. Then the presentation of data is done with tables and diagrams. The results showed that teachers and students have different perspectives on each e-learning platform supporting the learning process. Based on the philosophy of teachers and students, it can be stated that 1) teachers and students prefer Google Classroom to Edmodo as an LMS in Online Learning. This is because Google Classroom is easier to use, more interactive, and more efficient; 2) Google Meet is the application most often used and preferred by teachers and students in direct virtual Learning. Even though Zoom Cloud Meeting has a more attractive appearance and features, Google Meet is easier to access and considered to save internet quota; 3) As many as 43% of teachers and 49% of students prefer a combination of Google Classroom, Google Meet, WA Group to support the online learning process. Meanwhile, 41% of teachers and 42% of students prefer a combination of Google Classroom, Zoom Cloud Meeting, and WA Group as an e-learning platform. Only a few teachers and students choose the variety of Edmodo Zoom and WhatsApp groups and the combination of Edmodo, Google Meet, and WhatsApp groups.Keywords: E-Learning Platform, Student Perspective, Teacher Perspective